Aktivasi Nilai Pendidikan Dalam Konsep Aswaja - RAHEM, ZAITUR (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2016)
Education in Indonesia is like being in a tangled yarn winding. Growth is lush yet full of mud and moss. There is a happy face, but there was an air-rada rada black. Simply put, our education (Indonesia) like a ship sailing aimlessly and goals. Appeared later than this confusion about the various interpretations of education in Indonesia. Such as Character Education, Cultural Value-Based Education, Social, Religious and others. The times, the movement of ideas and seek solutions to the problems of education in Indonesia continues to grow. A number of researchers, experts and practitioners work together to look for the hallmark of education in Indonesia. Various methods and stratgei done in order to find distinctive character education formulations ness. There are various kinds of character education are taken from the values of both groups, a particular doctrine or custom. This new discovery is the responsibility of the observer forms, practitioners and education experts on wajahpendidikan in Indonesia. One of these ideas Aswaja Value-Based Character Education. Is this keaswajaan effective and could be part of the establishment of the nation's private good?